Pengembangan Sistem Informasi Media Promosi UMKM Menerapkan Metode User Centered Design - Viki Saputra; Deny Hidayatullah (STMIK Budi Darma, 2022)
One of the requirements of globalization in the business world is to integrate restaurant management with information systems and computerized technology. Therefore, the web is a medium and publication that can be easily searched anytime and anywhere through the internet without being limited by geographical areas that can be used for food vendors. The purpose of this research is to build a web-based advertising media system. The research flow is through collecting data through interviews, observation, documentation, and literature studies. by applying the User Centered Design process to the system using the Unified Modeling Language (UML). Apply the PHP programming language, create a front-end design using the Bootstrap framework, and a MySQL database to create a web. As part of this research, developed a web-based advertising medium for the Ketupat Sayur Uni Epi.